Correlation Between Bivalves Species Diversity with Water and Sediment Lead (Pb) Levels at Joko Moersodo Beach, Lamongan - Atika Jati, Ina Sintya; Sunu Kuntjoro (LenteraBio : Berkala Ilmiah Biologi, 2023)
Joko Moersodo Beach is on the north coast of East Java, Lamongan Regency to be precise. Joko Moersodo Beach is close to the Fish Landing Base, residential areas, and ponds, and is used as a tourism site, so it has a risk of being polluted by the heavy metal lead. Bivalvia are commonly found on Joko Moersodo Beach and are known to accumulate heavy metals, so they are used as aquatic bioindicators. The purpose of this study was to identify and describe the diversity of bivalves, and to analyze the correlation between the diversity of bivalves and the levels of lead in water and sediments at Joko Moersodo Beach. Sampling was carried out at three stations consisting of three sub-stations. At each sub-station a plot of 5x5 m is determined and there are sub-plots with an area of ​​1x1 m as many as five points. Water samples were measured with physico-chemical parameters. Testing for lead levels in water and sediments uses the Atomic Absorption Spectrophotometry method. Data were analyzed using the Pearson correlation test to determine the correlation between bivalve species diversity and water and sediment lead content at Joko Moersodo Beach. The results showed that the bivalves found on Joko Moersodo Beach consisted of seven species belonging to six genera and three families. The bivalve diversity index includes moderate diversity with moderately polluted waters. The correlation between bivalve species diversity and water and sediment lead content at Joko Moersodo Beach showed insignificant results.